Method for adequate macroscopic gallbladder examination after cholecystectomy. Issue 6 (1st November 2020) - Corten, Bartholomeus J. G. A.; Leclercq, Wouter K. G.; van Zwam, Peter H.; Roumen, Rudi M. H.; Dejong, Cees H.; Slooter, Gerrit D.
Abstract: Background and aims: There is no clear guideline nor protocol for macroscopic examination of the gallbladder, leaving surgeons extemporaneous in regard of gallbladder examination in selective histopathologic policy. The purpose of this article is to describe a surgical approach for adequate macroscopic inspection of the gallbladder. Materials and methods: The described practical method was developed in collaboration between surgeons and pathologists. This method was introduced in 2011 and implemented in 2012. We retrospectively reviewed the number of cholecystectomies and number of histopathologic examinations between 2006 and 2017, using our own patient database. We used the Netherlands Cancer Registry (NCR) to examine the incidence of gallbladder cancer patients before and after implementation of the selective policy in our hospital. In addition to the method, we depict several frequent macroscopic abnormalities in order to provide some examples for surgical colleagues. Results: Since implementation of the selective policy, 2271 surgical macroscopic gallbladder examinations were performed. As a result, we observed a significant decrease from 83% in 2012 to 38% in 2017, in histopathologic examination of the gallbladder following cholecystectomy. We observed a stable trend of gallbladder carcinoma in the same period (0.17%, n  = 4 during 2006–2011 and 0.26%, n  = 6 during 2012–2017). Conclusion: A simple, valid and easy method is described for future macroscopic analysis by the surgeon following a cholecystectomy.